Application of Flipped Classroom to Improve Learning Outcomes in Redox Reaction Lesson - Lestari Kurniawati Zai; Risnita Vicky Listyarini (Universitas Pendidikan Mandalika, 2023)
The present study assesses the effectiveness of the flipped classroom learning model in enhancing the learning outcomes of 10th-grade students in the subject of redox reaction concepts. A quasi-experimental design was employed using a one-group pretest-posttest approach. The samples of 20 students were selected through purposive sampling. Data were collected through learning outcome tests, performance assessments on worksheets (LKPD), learning performance observations, and response questionnaires. Descriptive analysis and N-Gain techniques were used to analyze the data.The results of the study indicate that the flipped classroom learning model had a positive effect on the students' learning outcomes, as reflected by an average N-Gain of 0.56 and 0.62 with a medium criteria in the first and second meetings, respectively. The students' performance on LKPD showed an average percentage of 91.5% and 97.5% categorized as excellent in the first and second meetings, respectively. Observations showed that the students' learning performance improved by 51% (first) to 78% on the second meeting. The students' responses to the application of the flipped classroom learning model were positive, with an average percentage of 72.1%. The findings of this study suggest that the flipped classroom learning model can be an effective alternative learning model, particularly in the teaching of redox reaction concept material.